Gender Bias at the Intersection of Engineering and Business: Implications for Workplace Education - Lisa Baumgartner; Jill Zarestky; Michelle Bigler; Malini Natarajarathinam (Adult Education Research Conference, 2018)
Abstract: STEM and business fields historically include pervasive gender biases. To better integrate women, and based on results of an industry survey, we propose ways adult education may address such biases.
Keywords: STEM; gender bias; Changing Mental Models Framework; workplace education